Ionic Liquid Control Crystal Growth to Enhance Planar Perovskite Solar Cells Efficiency. Issue 20 (29th July 2016) - Seo, Ji‐Youn; Matsui, Taisuke; Luo, Jingshan; Correa‐Baena, Juan‐Pablo; Giordano, Fabrizio; Saliba, Michael; Schenk, Kurt; Ummadisingu, Amita; Domanski, Konrad; Hadadian, Mahboubeh; Hagfeldt, Anders; Zakeeruddin, Shaik M.; et al.
Abstract : Ionic liquids can retard the perovskite crystallization with the aim to form compact films with larger and more uniformly distributed grain size. The ionic liquid driven crystallization is exploited to prepared a record planar perovskite solar cell with stabilized power output of 19.5%.